REVIEW ARTICLE: VALIDATION OF GAS CHROMATOGRAPHY-MASS SPECTROMETRY (GC-MS) METHODS IN THE ANALYSIS OF VOLATILE COMPOUNDS IN NATURAL MATERIALS - Fauzan, Ki Agus Rifki; Wea Bii, Maria Febriani; Salsabila, Atikah; Rahma, Siti; Wulandari, Destiana; Yanto, Ari (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2025)
Natural ingredients from plants are a major source of volatile compounds with biological activities such as antimicrobial, antioxidant, anti-inflammatory, and antifungal, particularly in essential oils. Testing of these compounds relies on reliable techniques such as gas chromatography-mass spectrometry (GC-MS), which separates and identifies components through retention time and mass spectra, with validation ensuring linearity, precision, accuracy, limit of detection (LOD), and limit of quantification (LOQ). This review article assesses the use and validation of GC-MS methods for the analysis of volatile compounds from natural ingredients, based on national and international literature over the past five years. The review approach included a structured search of databases such as PubMed, ScienceDirect, Google Scholar, and SINTA journals, with a focus on validation parameters and GC-MS instrument settings. The findings show that GC-MS stably detects key compounds such as monoterpenes and sesquiterpenes with 97-99% accuracy, and validates them according to AOAC standards (R² > 0.99; RSD < 8%; recovery 80-100%), where different extraction techniques affect their biological content and effectiveness. GC-MS validation is important to encourage innovation of environmentally friendly natural products in the pharmaceutical, food, and cosmetic sectors as a substitute for synthetic preservatives.